2019
DOI: 10.3892/mmr.2019.10565
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‑124‑3p protects against acute myocardial infarction by suppressing the apoptosis of cardiomyocytes

Abstract: The aims of the present study were to investigate the roles and underlying mechanisms of microrna-124-3p (mir-124-3p) in the progression of acute myocardial infarction (aMi). The expression of mir-124-3p was determined via reverse transcription-quantitative polymerase chain reaction (rT-qPcr). TargetScan analysis and a luciferase reporter assay were conducted to reveal the association between mir-124-3p and nuclear factor κ-light-chain-enhancer of activated B cells (nF-κB) repressing factor (nKrF). To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…In AMI rats, inhibiting the expression of miR-124-3p can reduce apoptosis, inflammation and oxidative stress ( 50 ). In the blood of patients with AMI and hypoxia-treated H9c2 cells, the expression of miR-124-3p was significantly increased ( 51 ). Further studies have demonstrated that downregulation of miR-124-3p can inhibit inflammation and cardiomyocyte apoptosis by regulating the activated B-cell suppressor factor (NKRF)/NF-κB pathway to prevent AMI ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AMI rats, inhibiting the expression of miR-124-3p can reduce apoptosis, inflammation and oxidative stress ( 50 ). In the blood of patients with AMI and hypoxia-treated H9c2 cells, the expression of miR-124-3p was significantly increased ( 51 ). Further studies have demonstrated that downregulation of miR-124-3p can inhibit inflammation and cardiomyocyte apoptosis by regulating the activated B-cell suppressor factor (NKRF)/NF-κB pathway to prevent AMI ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the blood of patients with AMI and hypoxia-treated H9c2 cells, the expression of miR-124-3p was significantly increased ( 51 ). Further studies have demonstrated that downregulation of miR-124-3p can inhibit inflammation and cardiomyocyte apoptosis by regulating the activated B-cell suppressor factor (NKRF)/NF-κB pathway to prevent AMI ( 51 ). Several miRNAs such as miR-17-3p, miR-34a, and miR-22 are reported to be involved in the pathophysiology of cell senescence ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the miRNA family, miRNA-124-3p correlates with the proliferation and apoptosis of cells [ 24 ]. Multiple researches have indicated the great importance of miR-124-3p in cardiovascular diseases [ 25 ]. The PTEN gene is the first novel tumor suppressor gene with specific phosphatase activity that was cloned in 1997 and can effectively inhibit the growth of tumor cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the hsa-mir-26a/b-5p was highly expressed in cardiac hypertrophy ( Tang et al, 2020 ) and promoted myocardial infarction-induced cell death ( Jung et al, 2021 ), yet overexpression of miR-26a/b attenuated cardiac fibrosis ( Tang et al, 2017 ; Wang et al, 2019 ) and alleviated cardiac hypertrophy and dysfunction ( Shi et al, 2021 ). Lastly, the hsa-mir-124-3p was reported to promote cardiac fibroblast activation and proliferation ( Zhu et al, 2021 ), and its inhibition protects against acute myocardial infarction by suppressing cardiomyocyte apoptosis ( Hu et al, 2019 ). Based on the duality effects of these miRNAs, the potential of these miRNAs as therapeutic targets for DMD-related cardiomyopathy need to be assessed carefully.…”
Section: Discussionmentioning
confidence: 99%